Smart Contracts in the Construction Industry: A New Era of Transparency and Efficiency - Ryan Adiputera; Fuk Jin Oei (Cantilever: Jurnal Penelitian dan Kajian Bidang Teknik Sipil, 2025)
Construction industry often faces challenges such as payment delays, contract disputes, and a lack of transparency and administrative efficiency. Smart contract technology based on blockchain offers an innovative approach to address these issues through transparent, automated, and tamper-resistant systems. This study explores various applications of blockchain and smart contracts in construction projects, including solutions for automated progress payments, digital contract management, quality improvement, and technology-based dispute resolution, using the Systematic Literature Review (SLR) method. Smart contract systems can execute payments automatically based on verified work progress, while blockchain technology ensures secure and immutable data recording. Additionally, integration with technologies such as Building Information Modeling (BIM) and the Internet of Things (IoT) enhances real-time project management. Despite offering numerous benefits, the implementation of these technologies still faces challenges such as regulatory uncertainty, infrastructure readiness, and the need for standardization. This study highlights that the adoption of blockchain and smart contracts holds significant potential to drive efficiency, fairness, and digital transformation in the construction sector.